Transformasi Digital dan Kinerja Keuangan: Bukti Empiris dari Bank yang Terdaftar di Bursa Efek Indonesia - Putri Shafira; Evi Gantyowati (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2025)
The banking sector has comprehensively adopted digital transformation to maintain operational efficiency and competitiveness, particularly after the pandemic. This study aims to analyze the impact of digital transformation on the financial performance of banking companies listed on the Indonesia Stock Exchange (IDX) during 2020–2023. Samples were selected using purposive sampling, resulting in 153 observations over four years. A quantitative approach was employed using secondary data from annual financial reports, analyzed with multiple linear regression. The findings indicate that digital transformation positively affects financial performance, especially through social media utilization. This highlights the need for banks to continuously adapt to technological developments, supported by government policies such as incentives, regulations, and digital infrastructure to strengthen Indonesia‘s digital banking ecosystem.